Model Bisnis dan Strategi Pengelolaan Ekowisata Berbasis Masyarakat Adat di dalam dan sekitar Taman Nasional Danau Sentarum (Ekowisata Dusun Meliau) - Wiwit Astari; Yooce Yustiana; Nandang Prihadi (Faculty of Forestry Universitas Gadjah Mada, 2023)
Danau Sentarum National Park (DSNP), situated in West Kalimantan's Kapuas Hulu region, stands out as a unique destination. Meliau Hamlet, located within and around DSNP, servesasasettlementfortheDayak Ibantribe, preserving theirdistinctcustoms. The surrounding area boasts captivating landscapes, including lakes, swamps, rivers, and hills, drawing both domestic and international tourists. Recognizing this potential, the Melemba Village government established KPP Kaban Mayas, an ecotourism initiative. However, challenges such as limited human resources, insufficient infrastructure, and management issues hindered Meliau Hamlet's ecotourism operations. This research aimed to assess ecotourism development feasibility, economic viability, and community engagement. It also outlined the ecotourism management's business model and strategies. Data was gathered through field visits, interviews, and surveys. Analysis encompassed scoring tourist attractions, evaluating stakeholders, financial assessments, and community capital. The Business Model Canvas (BMC) described the business model, while strategies were formulated using SWOT analysis, Quantitative Strategic Planning Matrix (QSPM), and Blue Ocean Strategy (BOS). Results underscored natural resources as vital assets for ecotourism. Meliau Hamlet's ecotourism could thrive by focusing on value proposition, keyresources, keyactivities, and keypartnerships.